Opportunities and challenges for the application of microfluidic technologies in point-of-care veterinary diagnostics. Issue 5 (October 2016) - Busin, Valentina; Wells, Beth; Kersaudy-Kerhoas, Maïwenn; Shu, Wenmaio; Burgess, Stewart T.G.
Abstract: There is a growing need for low-cost, rapid and reliable diagnostic results in veterinary medicine. Point-of-care (POC) tests have tremendous advantages over existing laboratory-based tests, due to their intrinsic low-cost and rapidity. A considerable number of POC tests are presently available, mostly in dipstick or lateral flow formats, allowing cost-effective and decentralised diagnosis of a wide range of infectious diseases and public health related threats. Although, extremely useful, these tests come with some limitations. Recent advances in the field of microfluidics have brought about new and exciting opportunities for human health diagnostics, and there is now great potential for these new technologies to be applied in the field of veterinary diagnostics. This review appraises currently available POC tests in veterinary medicine, taking into consideration their usefulness and limitations, whilst exploring possible applications for new and emerging technologies, in order to widen and improve the range of POC tests available. Highlights: Current state of the art for point-of-care testing in veterinary medicine. Animal diseases where point-of-care tests are of particular importance. Possible future application of emerging microfluidic technologies in veterinary diagnostics.